Volume Stratification for Stratified Sampling Through Pilot Survey with Aerial Photographs - Tiwari, K. P. (Indian Forester, 1977)
Basic data to plan resources survey are obtained through pilot surveys. Such datas may be regarding terrain, accessibility, extent and Dature of the forest, range and variability of volume for stratified satnpling designs. In pilot survey of Karirnnagar district (AP) aerial photographs on 1 : 40,000 scale were used, and forest area classified on the basis of species, height and crown closure. Mean volume per hectare in each forest type was obtained from the ground. Ten strata were grouped into three strata on the basis of Duncan's multiple range teat aDd nDge variability and basic of volume stratification envolved for further surveys.